Structure and electrical properties of Mg-doped ZnO nanoparticles - Kilinc, N.; Arda, L.; Ozturk, S.; Ozturk, Z. Z. (Wiley-V C H Verlag Gmbh, 2010)
MgxZn1-xO (x=0.01-0.3) nanoparticles were synthesized by the sol-gel technique using solutions of Mg and Zn based organometalic compounds. The electrical properties of Mg doped zinc oxide (ZnO) were studied within wide temperature range from 300 to 500 K under the N-2 gas flow (flow rate: 20 sccm) and in the frequency range from 40 Hz to 1 MHz for ac electrical measurements. The de conductivities and the activation energies were found to be in the range of 10(-9)-10(-6) S/cm at the room temperature and 0.26-0.86 eV respectively depending on doping rate of these samples. The ac conductivity was well represented by the power law A omega(s). The conduction mechanism for all doped ZnO could be related to correlated barrier hopping (CBH) model. The complex impedance plots (Nyquist plot) showed the data points lying on a single semicircle, implying the response originated from a single capacitive element corresponding to the nanoparticle grains. The crystal structures of the MgxZn1-xO nanoparticles were characterized using X-ray diffraction. The calculated average particle sizes values of Zn1-xMgxO samples are found between 29.72 and 22.43 nm using the Sherrer equation. (C) 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim
Keywords: Mg doped ZnO; nanoparticle; conductivity; CBH; microstructure; impedance spectroscopy